Phát biểu của Chủ tịch Quốc hội Nguyễn Sinh Hùng bế mạc kỳ họp thứ 10, Quốc hội khóa XIII (Ngày 27/11/2015) - Nguyễn Sinh Hùng (2015)
Phát biểu của Chủ tịch Quốc hội Nguyễn Sinh Hùng bế mạc kỳ họp thứ 10, Quốc hội khóa XIII (Ngày 27/11/2015)